Applications of passive organic track detector in nuclear, material and environmental sciences - Baykara, Oktay; Do?ru, Mahmut (Nova Science Publishers, Inc., 2010)
Track detectors were discovered by Young, Silk and Barner, and they have beenwidely used in science and technology. Detection technique based on using trackdetectors and presently called solid state nuclear track detection (SSNTD). The varioustypes of passive track detectors, for example CR-39, LR 115, DNC and Makrofol E havedifferent etching technique and maximum detectable energy ranges of alpha particles,carried out in large number of fields involving different aspect of nuclear, material andenvironmental science. Briefly, some of these fields are archeology, cosmology,biophysics, particle physics (e.g., exotic phenomena), geochronology, seismology (e.g.,earthquake prediction), metallurgy, nuclear physics and medical studies. This techniqueused in all above various fields based on detection of charged particles with solid statetrack detectors. Shortly, this chapter condenses on the applications of this technique inthe various scientific areas. © 2010 Nova Science Publishers, Inc. All rights reserved.
Keywords: Organic track detector; Radiation detection; Science; Technology